Agrotóxicos: uma revisão sobre a história, sua classificação, usos e impactos ambientais com enfoque na agroecologia e na inovação aberta como alternativas sustentáveis - Florido, Anna Laura Lionello (Universidade Federal de São Carlos, 2021)
Pesticides are mentioned with great frequency in the media, and scientific articles, presenting positive and negative points about them. This work aimed to review general information about pesticides, presenting some definitions, classifications, applications and toxicities. Moreover, the consequences of the indiscriminate use of pesticides and the new technologies were analyzed. A new economy model that takes advantage of open innovation is also discussed, in which cooperation between large companies, startups and universities can directly contribute to more sustainable solutions and better use of resources. It is concluded with this review that the use of pesticides were/are essential for agricultural production, but that there are new technologies, as agroecology, that enable sustainable production.
Pesticides: a review of the history, classification, uses and environmental impacts focusing on agroecology and open innovation
Keywords: Agrotóxicos; Agroecologia; Inovação Aberta; Pesticides; Agroecology; Open Innovation; CIENCIAS EXATAS E DA TERRA::QUIMICA